A novel small molecule approach for the treatment of propionic and methylmalonic acidemias - Armstrong, Allison J.; Collado, Maria Sol; Henke, Brad R.; Olson, Matthew W.; Hoang, Stephen A.; Hamilton, Christin A.; Pourtaheri, Taylor D.; Chapman, Kimberly A.; Summar, Marshall M.; Johns, Brian A.; Wamhoff, Brian R.; Reardon, John E.; et al. (Molecular genetics and metabolism, 2021)
Propionic Acidemia (PA) and Methylmalonic Acidemia (MMA) are inborn errors of metabolism affecting the catabolism of valine, isoleucine, methionine, threonine and odd-chain fatty acids. These are multi-organ disorders caused by the enzymatic deficiency of propionyl-CoA carboxylase (PCC) or methylmalonyl-CoA mutase (MUT), resulting in the accumulation of propionyl-coenzyme A (P-CoA) and methylmalonyl-CoA (M-CoA in MMA only). Primary metabolites of these CoA esters include 2-methylcitric acid (MCA), propionyl-carnitine (C3), and 3-hydroxypropionic acid, which are detectable in both PA and MMA, and methylmalonic acid, which is detectable in MMA patients only (Chapman et al., 2012). We deployed liver cell-based models that utilized PA and MMA patient-derived primary hepatocytes to validate a small molecule therapy for PA and MMA patients. The small molecule, HST5040, resulted in a dose-dependent reduction in the levels of P-CoA, M-CoA (in MMA) and the disease-relevant biomarkers C3, MCA, and methylmalonic acid (in MMA). A putative working model of how HST5040 reduces the P-CoA and its derived metabolites involves the conversion of HST5040 to HST5040-CoA driving the redistribution of free and conjugated CoA pools, resulting in the differential reduction of the aberrantly high P-CoA and M-CoA. The reduction of P-CoA and M-CoA, either by slowing production (due to increased demands on the free CoA (CoASH) pool) or enhancing clearance (to replenish the CoASH pool), results in a net decrease in the CoA-derived metabolites (C3, MCA and MMA (MMA only)). A Phase 2 study in PA and MMA patients will be initiated in the United States.